Assessment of Carbon Status in Marine Protected Area of Payung Island Waters, South Sumatera Province, Indonesia - Anna Ida Sunaryo Purwiyanto; Fitri Agustriani (Marine Science Department Diponegoro University, 2017)
CO2 is a greenhouse gas that receive more attention than the other gases because the properties of carbon easily deformed and diffuseed. Changes in the concentration of CO2 in the water will impact on changes in the amount of CO2 in the atmosphere that affect sea surface temperatures. It continuously will result in a change of marine capture fisheries. Payung Island is one of the important areas in South Sumatra that acts as the provider of the fishery. This because Payung Island is located in the mouth of Musi and Telang River covered by mangrove, has a very important ecological function. However, the condition of the carbon in the waters of the Payung Island has not explored further. This elementary study is to determine status on Payung Island waters as a sink or source of CO2. The study was conducted in June until August 2015. The research stages include surface water sampling, measurement of the CO2 in the atmosphere, the analysis of the concentration of Dissolved Inorganic Carbon (DIC) and Total Alkalinity (TA), and partial pressure of carbon dioxide (pCO2) calculation. Atmospheric CO2 were measured insitu, while the DIC and TA were analyzed using titration methods. Partial pressure of carbon dioxide (pCO2) obtained from the calculation using the software CO2Calc using data of DIC, TA, nutrients and atmospheric CO2. The results showed that the content of DIC and TA on the Payung Island waters has similar distribution pattern i.e. high in areas close to the river, and getting lower in the area which were closer to the sea. The comparisons between pCO2 atmosphere and pCO2 waters showed that Payung Island waters generally act as a carbon sink in area towards the sea but however, in the territorial waters adjacent to the river as a source of carbon. Keywords: carbon, marine protected area, Payung Island waters